Penilaian Kemampuan Computational Thinking (Pemikiran Komputasi) - Miksan Ansori (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Computational thinking emphasizes high order thinking rather than real performance such as portfolios or other tangible evidence. Thought processes in computational thinking such as abstraction, decomposition, generalization, critical analysis in finding mass solutions and removing obstacles in them all occur in actual in the student's brain causing difficulty in its measurement. Therefore, computational thought measurement and assessment is an important capability to study. In this study will discuss how computational thought measurement solving problems that can be used as a reference in determining the success of curriculum that previously did not have a clear benchmark.